Development of learning media patisserie based on hybrid learning. Issue 4 (March 2021) - Rahmawati, Y; Yogha, S; Maosul, A
Abstract: Utilization of the internet in patisseries learning is not optimal yet, the use of media in learning is not entirely interesting and varied, task collection and evaluation of learning outcomes are still print-based, one of the difficulties associated with technical issues is understanding the material and collecting assignments. These three factors are the background of the learning management system in the implementation of hybrid learning based patisseries. Learning Management System is one way to develop online learning or e-learning, which is a web-based learning management application that facilitates learners to learn as they should in a virtual classroom. The Learning Management System used in this study is a Web-based Learning Management System that is available at https://spot.upi.edu/. The design of the Learning Management System model in Patisserie learning is useful to assist in the teaching and learning process. Learning programs based on the use of internet technology (online) that can be done without the limitation of space and time 'any time anywhere'. This Learning Management System application model, made based on the web, with the aim to enable lecturers and students who become the user model of this application, to access learning plans and learning material through the internet wherever they are. Supporting facilities in the form of network and network server at UPI have reached 800 Mbps, then from the SPOT process aspects using licensed software namely Microsoft Office and hardware +-970 with the core 2 processor, P4 flat slim monitor. In addition to accessing learning material, this learning management system helps users to be able to discuss topics by on-line using the forum provided. This study aims to develop a hybrid learning based learning management system for the readiness of students' competency test.